Energy and potassium ion homeostasis during gamma oscillations - Kann, Oliver; Hollnagel, Jan-Oliver; Elzoheiry, Shehabeldin; Schneider, Justus (Frontiers in molecular neuroscience, 2016)
Fast neuronal network oscillations in the gamma frequency band (30-100 Hz) occur in various cortex regions, require timed synaptic excitation and inhibition with glutamate and GABA, respectively, and are associated with higher brain functions such as sensory perception, attentional selection and memory formation. However, little is known about energy and ion homeostasis during the gamma oscillation. Recent studies addressed this topic in slices of the rodent hippocampus. Methods with high spatial and temporal resolution were applied, such as electrophysiological recordings of local field potential (LFP) and extracellular potassium concentration ([K+]o), live-cell fluorescence imaging of NAD(P)H and FAD (cellular redox state), and monitoring of the interstitial partial oxygen pressure (pO2) in depth profiles with microsensor electrodes, including mathematical modelling. The main findings are: (i) gamma oscillations are associated with high oxygen consumption rate and significant changes in the cellular redox state, indicating rapid adaptations in glycolysis and oxidative phosphorylation. (ii) Gamma oscillations are accompanied by fluctuating elevations in [K+]o of less than 0.5 mmol/L from baseline, likely reflecting effective K+-uptake mechanisms of neuron and astrocyte compartments. (iii) Gamma oscillations are exquisitely sensitive to metabolic stress induced by lowering oxygen availability or by pharmacological inhibition of the mitochondrial respiratory chain. These findings reflect precise cellular adaptations to maintain ATP, ion and neurotransmitter homeostasis and thus neural excitability and synaptic signaling during gamma oscillations. Conversely, the exquisite sensitivity of gamma oscillations to metabolic stress might significantly contribute the exceptional vulnerability of higher brain functions in brain disease.
Gesehen am 07.05.2020